Implementasi Sistem Informasi Kearsipan dan Pelacakan Surat Berbasis Web di BAZNAS Kabupaten Kudus - Sulung, Bagus Putra; Arifin, Muhammad (Al-DYAS, 2026)
Although the digitalization of public administration has been widely studied, its application within socio-religious institutions such as BAZNAS remains underexplored. This study aims to evaluate the effectiveness of implementing a web-based Archival and Mail Tracking Information System in improving the efficiency, accuracy, and transparency of administrative governance at BAZNAS of Kudus Regency. A mixed-method approach was employed using a Participatory Action Research (PAR) design, involving the active participation of selected BAZNAS staff through purposive sampling. Data were collected through observation, interviews, and questionnaires, and analyzed using thematic and descriptive analysis techniques. The results demonstrate that the implementation of the digital system improved administrative record accuracy, accelerated mail handling processes, and enhanced public service transparency—particularly through the online tracking feature that enables mustahik to monitor the status of their correspondence in real time. These findings highlight the strategic role of archival digitalization in strengthening bureaucratic efficiency, increasing accountability, and building public trust in zakat management. The study concludes by emphasizing the importance of adopting participatory digital systems in religious institutions and recommends replicating this model in similar organizations as part of a broader effort to advance value-based digital transformation in public services.